2016
DOI: 10.3390/challe7010003
|View full text |Cite
|
Sign up to set email alerts
|

Practical Eco-Design and Eco-Innovation of Consumer Electronics—the Case of Mobile Phones

Abstract: Annually, it is estimated that about 4 billion units of consumer electronics for mobile communications are produced worldwide. This could lead to various ecological imbalances unless the design and disposal of the products are handled optimally. To illustrate how industry looks at and responds to the increasing social awareness, this article describes how sustainability is successfully implemented in practice at a large Chinese company, developing and producing various kinds of electronic products used for com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 81 publications
0
16
0
Order By: Relevance
“…If the operation and conditions of the equipment cannot be recovered, its components and materials are used for repair or to remanufacture other products. To achieve this, a modular eco-design of the parts and components is required for the materials to be recovered; otherwise, they are incinerated or safely disposed of [35][36][37][38].…”
Section: Ce In the Electrical And Electronics Industrymentioning
confidence: 99%
“…If the operation and conditions of the equipment cannot be recovered, its components and materials are used for repair or to remanufacture other products. To achieve this, a modular eco-design of the parts and components is required for the materials to be recovered; otherwise, they are incinerated or safely disposed of [35][36][37][38].…”
Section: Ce In the Electrical And Electronics Industrymentioning
confidence: 99%
“…Andrae and Vaija [4] suggested that eco-rating LCA methods [25] show similar results as further simplified methods. Andrae et al [3] explained how eco-rating is linked to eco-design and argued that OLCA facilitates a balance between improved material efficiency and linearly increasing GWPI scores.…”
Section: Open Eco Rating Lcamentioning
confidence: 99%
“…As such smartphone sales are currently around 1500 million units and tablets around 350 million [1]. Smartphones usually have a relatively short operating lifetime of 2 to 4 years which negatively influences eco-environmental impacts such as abiotic resource depletion (ARD) and climate change (CC) [3].…”
Section: Introductionmentioning
confidence: 99%
“…Several companies are implementing sustainable logistics to increase their supply chain competitiveness [19][20][21]. According to Leigh and Li, in order to develop environmental sustainable supply chains, approaches such as ecodesign, recycling, reuse or remanufacturing can be used [22][23][24].…”
Section: Introductionmentioning
confidence: 99%